Pattern and Prevalence of Dyslipidemia among Patients with Acute Coronary Syndrome Admitted in a Tertiary Level Hospital (Bangladesh Heart Journal, 2019)
Background: The leading cause of mortality in men and women worldwide is coronary artery disease (CAD). For hospitalization in our country, acute coronary syndrome (ACS) is a major reason. Dyslipidemia is found one of the most important modifiable risk factors for CAD.Aim: The aim of the study was to determine the pattern and prevalence of dyslipidemia among patients with ACS admitted in National Institute of Cardiovascular Diseases (NICVD), Dhaka.Subjects and methods: One thousand (1000) patients with ACS were included and classified according to clinical presentation, the findings on the admission electrocardiogram (ECG) and the results of serial cardiac troponin levels, into myocardial infarction(MI), either STelevation or non ST- elevation MI, and unstable angina(UA) subgroups. In the other group 500 healthy subjects were included as controls. All subjects were subjected determination lipid profile. ECG and Troponin- I were done for diagnosis and follow up of the patients.Results: In patients with ACS, high levels of TC (>200 mg/dl) were found in 60.67%,high levels of LDL (> 130 mg/dl) were found in 58%, high levels of TG (>150 mg/ dl) were found in 63.33%, however, low levels of HDL (< 40 mg/dl) were found in 66%. There was a statistically significant elevation in TC, LDL, TG serum levels in patients with ACS compared to control subjects (p 4 were significantly higher in patients with ACS than controls. There was no significant difference between MI and UA patients regarding all lipid profile parameters. TC, LDL, TG were significantly higher in males than in females while HDL was significantly higher in females compared to males. Also TC/HDL and TG/HDL ratios were significantly higher in males compared to females. All lipid components were significantly more prevalent in males than in females except TG where there was no significant difference between males and females. Stepwise regression analysis of lipid parameters revealed that TC/HDL and TG/HDL ratios were independent risk factors for ACS.Conclusion: Dyslipidemia is one the major risk factors which is widely prevalent in patients with ACS and is more prevalent in males than in females. We recommend paying more attention to serum lipids and other modifiable risk factors for prevention of ACS and more studies about them as risk factors of atherosclerosis and its impact on other systems is advised.Bangladesh Heart Journal 2019; 34(1) : 31-36